Xanthine Oxidase Inhibitory Activity of Some Malaysian Plants - , M, Vikneswaran; K.L, Chan, (Malaysian Journal of Science, 2005)
Inhibition of xanthine oxidase (XO) is an effective therapeutic approach for treating hyperuricemia that causes gout. Methanol extracts of nine Malaysian medicinal plants, namely Blumea balsamifera, Orthosiphon stamineus, Alyxia lucida, Andrographis paniculata, Eurycoma longifolia, Ardisia crispa, Smilax myosotiflora, Zebrina pendula and Tinospora crispa were assayed for XO inhibitory activity. The enzymatic activity was estimated by measuring the increase in absorbance at 292 nm due to uric acid formation. Allopurinol, a known inhibitor of xanthine oxidase, was used to validate the method and was adopted as positive control in the studies. The accuracy of the enzymatic assay method was found to be satisfactory (CV < 12.25 %) and IC₅₀ of allopurinol was 0.022 µ/ml. Of the plants tested, five were found to have more than 25 % inhibition at a concentration of 100 µ/ml in the assay mixture. Blumea balsamifera exhibited the highest activity (IC₅₀ = 1.15 µ/ml). The IC₅₀ values of O. stamineus, A. lucida, A. paniculata and T. crispa were 30.79, 63.19, 230.18 and 370.35 µ/ml respectively.